A Determinants of Sleep Quality Among Postoperative Patients in Surgical Wards A Cross-Sectional Analysis - Rosy Cahyani Nababan (Professorline, 2025)
Sleep disturbances are common among postoperative patients and can significantly delay healing, elevate pain perception, and reduce psychological well-being. Multiple interrelated factors—including pain, anxiety, and environmental discomfort are believed to influence postoperative sleep quality, yet limited evidence exists in Indonesian hospital contexts. This study aimed to determine the relationship between environmental comfort, anxiety, and pain intensity with sleep quality among postoperative patients in surgical wards. A cross-sectional analytical survey was conducted in the Surgical Ward of the Regional General Hospital (RSUD) Makassar, Indonesia. A total of 60 postoperative patients were selected using accidental sampling. Data were collected through structured questionnaires and standardized instruments: the Hamilton Anxiety Rating Scale (HARS), the Numeric Rating Scale (NRS) for pain, and a Guttman-based questionnaire for environmental comfort and sleep fulfillment. Statistical analysis was performed using the Chi-Square test with a significance level of p < 0.05. Findings revealed that 68.3% of patients experienced moderate-to-severe pain, 63.3% reported anxiety, and 55% perceived their ward environment as uncomfortable. Sleep inadequacy was reported by 65% of respondents. Significant associations were found between sleep fulfillment and pain intensity (p = 0.00), anxiety (p = 0.00), and environmental comfort (p = 0.00). Pain, anxiety, and environmental comfort are key determinants of sleep quality in postoperative patients. These findings underscore the need for holistic nursing interventions that integrate physical, psychological, and environmental care to promote optimal recovery and patient well-being.